Biocompatibility of "On‐command" dissolvable tympanostomy tube in the rat model. (31st October 2016) - Mai, Johnny P.; Dumont, Matthieu; Rossi, Christopher; Cleary, Kevin; Wiedermann, Joshua; Reilly, Brian K.
Abstract : Objectives/Hypothesis: A prototype tympanostomy tube, composed of polybutyl/methyl methacrylate‐co‐dimethyl amino ethyl methacrylate (PBM), was tested to 1) evaluate the effect of PBM tubes on rat dermis as a corollary for biocompatibility and (2) to observe the efficacy of dissolution with isopropyl alcohol (iPrOH) and ethanol (EtOH). Study Design: Original animal experiment and bench testing. Methods: A two‐part study was conducted to assess biocompatible substance with inducible dissolvability as a critical characteristic for a newly engineered tympanostomy tube. First, tympanostomy tubes were inserted subcutaneously in 10 rats, which served as an animal model for biosafety, and compared to traditional tubes with respect to histologic reaction. Tissue surrounding the PBM prototype tubes was submitted for histopathology and demonstrated no tissue reactivity or signs of major inflammation. In the second part, we evaluated the dissolvability of the tube with either isopropyl alcohol, ethanol, ofloxacin, ciprodex, water, and soapy water. PBM tubes were exposed to decreasing concentrations of iPrOH and EtOH with interval qualitative assessment of dissolution. Results: Histologic examination did not reveal pathology with PBM tubes. Concentrations of at least 50% iPrOH and EtOH dissolve PBM tubes within 48 hours, whereas concentrations of at least 75% iPrOH and EtOH were required for dissolution when exposure was limited to four 20‐minute intervals. Conclusions: PBM is biocompatible in the rat model. Additionally, PBM demonstrates rapid dissolution upon alcohol‐based stimuli, validating the proof‐of‐concept of dissolvable on‐command or biocommandible ear tubes. Further testing of PBM is needed with a less ototoxic dissolver and in a better simulated middle ear environment before testing can be performed in humans. Level of Evidence: NA Laryngoscope, 127:956–961, 2017